2010
DOI: 10.1111/j.1745-4514.2009.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

LIPOXYGENASE ACTIVITY IN PRICKLY PEAR FRUIT (OPUNTIA FICUS INDICA[L.] MILL. CACTACEAE)

Abstract: Prickly pear LOX activity was detected in the membrane fractions of the fruit extracts at various stages of ripening. LOX specific activity was very low in the fruit of wild plants at the green stage (0.49 ± 0.04) and increased with fruit ripening, more than doubling in the ripened fruit (1.22 ± 0.06). Moreover, it was not influenced by the cultivar, whereas it was considerably increased (13.3 ± 1.4) by agronomic processes to which prickly pear plants are submitted to improve the organoleptic properties of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…97 kDa protein for TomloxB gene in tomato; Lv et al () have predicted a protein molecular weight of 103 kDa for DkLox1 gene in persimmon fruit; Schiller et al () reveled proteins with a molecular mass of about 101–105 kDa in apple fruit. Likewise, in non‐climacteric fruit Palmieri et al () calculated a molecular mass of 98 kDa for olive LOX; De Gregorio, Arena, and Giuffrida () reported an apparent molecular mass of 96 kDa in prickly pear fruit; and Leone et al () showed two groups of approximately 100 and 98 kDa for strawberry fruit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…97 kDa protein for TomloxB gene in tomato; Lv et al () have predicted a protein molecular weight of 103 kDa for DkLox1 gene in persimmon fruit; Schiller et al () reveled proteins with a molecular mass of about 101–105 kDa in apple fruit. Likewise, in non‐climacteric fruit Palmieri et al () calculated a molecular mass of 98 kDa for olive LOX; De Gregorio, Arena, and Giuffrida () reported an apparent molecular mass of 96 kDa in prickly pear fruit; and Leone et al () showed two groups of approximately 100 and 98 kDa for strawberry fruit.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the abundant information about the LOX isoforms in most plants, to the best of our knowledge, there are no reports available on chayote LOX isoforms or their activity. These may vary in relation to substrate preference, kinetic parameters, and the positional specificity of substrate oxygenation; additionally, LOX pathway are also involved in plant morphogenesis and senescence, fruit development, as well as plant response to stress and wounding (De Gregorio et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Probablemente la falta de luz durante el almacenamiento contribuyó a la desaparición de este volátil. Se ha reportado que el 2-nonenol se origina del ácido 9-hidroperoxi-linoleico y contribuye al 30% del olor en tuna (De Gregorio et al, 2010).…”
Section: Presente En Nopal Frescounclassified